Impact Factor and other metrics for evaluating science: essentials for public health practitioners (Italian Journal of Public Health, 2011)
The quality of scientific evidence is doubly tied with the quality of all research activities that generatesit (including the “value” of the scientists involved) and is usually, but not always, reflected in thereporting quality of the scientific publication(s). Public health practitioners, either at research, academicor management levels, should be aware of the current metrics used to assess the quality value of journals,single publications, research projects, research scientists or entire research groups. However, this task iscomplicated by a vast variety of different metrics and assessment methods. Here we briefly review the mostwidely used metrics, highlighting the pros and cons of each of them. The rigid application of quantitativemetrics to judge the quality of a journal, of a single publication or of a researcher suffers from many negativeissues and is prone to many reasonable criticisms. A reasonable way forward could probably be the use ofqualitative assessment founded on the indications coming from few but robust quantitative metrics.
Keywords: peer review; bibliometric indicators; impact factor; h-index; eigenvalue; webometric indicators; g-index